2021
DOI: 10.1002/pc.26462
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interwoven roselle/sisal fiber reinforced epoxy composites

Abstract: The present work deals with the characterization of interwoven roselle/sisal fiber fabric reinforced epoxy composites. All the composites are manufactured using the hand layup technique, and the physical (density), mechanical (tensile, flexural, and impact) and dynamic mechanical characteristics are determined as per ASTM standards. The findings reveal that roselle fabric composite has superior mechanical properties than interwoven roselle/sisal fabric composites. The tensile and impact strengths of the sisal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Similarly, Figure 2C,D reveal that the hybridization of flax fiber and kenaf fiber increased the tensile strength, tensile modulus, flexural strength, and flexural modulus values by 60.26%, 33.94%, 125.75%, and 82.67% compared with pure PP, and by 31.16%, 5.69%, 66.64%, and 19.72% compared with pure kenaf (wKWK) composites. Similar behavior was reported by Kazi et al [ 18 ] in which roselle‐sisal hybrid composites with roselle fiber in the warp direction and sisal fiber in the weft direction exhibited superior mechanical properties.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Similarly, Figure 2C,D reveal that the hybridization of flax fiber and kenaf fiber increased the tensile strength, tensile modulus, flexural strength, and flexural modulus values by 60.26%, 33.94%, 125.75%, and 82.67% compared with pure PP, and by 31.16%, 5.69%, 66.64%, and 19.72% compared with pure kenaf (wKWK) composites. Similar behavior was reported by Kazi et al [ 18 ] in which roselle‐sisal hybrid composites with roselle fiber in the warp direction and sisal fiber in the weft direction exhibited superior mechanical properties.…”
Section: Resultssupporting
confidence: 88%
“…The mechanical properties of composites with woven fabrics are affected by several parameters, including yarn type, fiber content, fiber‐matrix adhesion, and yarn interlocking. [ 18 ] The orientation of the fibers in the longitudinal and transverse directions influences the load distribution between the fibers and, consequently, the ultimate strength behavior of composites. Tests on single fibers revealed that jute and flax fibers have the better tensile strength.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations